Analysis of Facilities and Infrastructure at SMPS Cisadane Mandiri - Adina Indriani; Emilya Sukma Dara Damanik; Irma Damayanti Lubis; Nuri Yanni Siregar (English Teaching and Linguistics Journal (ETLiJ), 2022)
Education is a protracted process and must continue as people age. Quality education will certainly produce human resources who can develop the potential of other resources in the country. This study aims to determine the completeness of facilities and infrastructure at SMPS Cisadane Mandiri. The needs analysis was carried out by conducting a qualitative descriptive approach with data obtained from the results of interviewing respondents, namely the principal. Findings show that there are still many facilities and infrastructure that are lacking such as the Science Laboratory, UKS, Student Council Room, Place of Worship and Guidance and Counseling Room so that the learning process is still inadequate but for management and administration at SMPS Cisadane Mandiri has a good system.Keywords: Analysis, Facilities and Infrastructure, Learning Process